2011
DOI: 10.1007/s00264-010-1205-3
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injection of tranexamic acid reduces not only blood loss but also knee joint swelling after total knee arthroplasty

Abstract: Purpose This is a randomised controlled trial to examine whether intra-articular injection of tranexamic acid (TXA) decreases blood loss, as well as reducing leg swelling after total knee arthroplasty (TKA). Methods We performed 100 TKA in osteoarthritis patients. At closure, a total of 2,000 mg/20 ml TXA was injected into the knee joint through a closed suction drain (TXA group). For the control group, the same volume of physiological saline was injected. The pre-operative condition of the patients, post-oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
194
3
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(214 citation statements)
references
References 25 publications
9
194
3
8
Order By: Relevance
“…Zohar et al (27) implants (30)(31)(32)(33) and favored based on the concern that systematic administration of IV-TXA might potentially increase the risk of thrombosis (34). In contrast, the TEG data obtained in the current study suggest that IV-TXA did not promote hypercoagulation since the mean CI in the TXA and FS + TXA groups was less than +3 and this CI remained similar to that of the control group during hospitalization.…”
Section: Discussioncontrasting
confidence: 53%
“…Zohar et al (27) implants (30)(31)(32)(33) and favored based on the concern that systematic administration of IV-TXA might potentially increase the risk of thrombosis (34). In contrast, the TEG data obtained in the current study suggest that IV-TXA did not promote hypercoagulation since the mean CI in the TXA and FS + TXA groups was less than +3 and this CI remained similar to that of the control group during hospitalization.…”
Section: Discussioncontrasting
confidence: 53%
“…Therefore, the plasma values that Wong et al, have measured might be misleading. Ishida et al, [6] Sa-Ngasoongsong et al, [7] and Roy et al, [8] have conducted similar studies recently, but both of them have used normal saline placebos.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier an intravenous (IV)dose in various doses have been used by many surgeons and their results have been extensively studied. [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14] Oral TXA has shown to have equal efficacy by Zohar et al [1] Nowadays, there is a increase interest in usage of intraarticular administration [2] and many others [6], [7], [8] have shown good outcome for intraarticular administration of this drug in TKA. But all of them have compared intraarticular administration of TXA with placebo controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Topical use of TA has been becoming popular recently as it has the advantages of being easy to administer, providing a maximum concentration at the bleeding site, and inducing partial microvascular hemostasis by stopping fibrin clot dissolution in the affected area. Some studies about topical administration of TA showed reliable evidence that it was effective in reducing total blood loss and blood transfusion rate compared with the placebo [5][6][7][8][9] and also intravenous (IV) administrations. Topical use of TA has been shown to reduce postoperative swelling, leading to improved wound healing, reduced pain, and more rapid rehabilitation.…”
mentioning
confidence: 99%